Tinjauan Hukum terhadap Putusan Bawaslu atas Dugaan Penggunaan Ijazah Palsu dalam Pencalonan DPRD Kota Kendari pada Pemilu 2024 - Ruslan, Ruslan; Dagani, Gamlan; Mpesau, Alasman (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2025)
ABSTRACT: The Election Supervisory Body (Bawaslu) has the authority to receive, examine, assess, and decide on administrative violations in elections, including allegations of using fraudulent diplomas during the candidacy process for members of district/city regional legislative councils (DPRD). This study aims to review Koreki Bawaslu RI Decision No. 029/KS/ADM/PL/BWSL/00.00/V/2024, which upheld the Decision of Bawaslu Kota Kendari No. 001/LP/ADM.PL/BWSL.KOTA/28.01/IV/2024, stating that the Kendari City General Election Commission (KPU) had carried out the DPRD candidacy process in accordance with electoral administrative procedures and mechanisms. However, the Directorate of Community and Special Education of the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia, through Letter No. 1429/C6/GT.03.03/2024 dated May 10, 2024, indicated that the DPRD Kendari City candidate, identified as LA or LR, was not registered as a participant in the 2008 National Equivalency Examination, which implies that the candidate was not entitled to possess an equivalency Package C diploma. This study employs a normative juridical method to analyze the legal basis of the decision. The findings reveal that Bawaslu Kota Kendari made errors in its legal considerations when ruling on the alleged administrative electoral violation regarding the use of a fraudulent diploma by the Kendari City DPRD candidate.